Ecology of Alpine Macrofungi - Combining Historical with Recent Data - Brunner, Ivano; Frey, Beat; Hartmann, Martin; Zimmermann, Stephan; Graf, Frank; Suz, Laura M.; Niskanen, Tuula; Bidartondo, Martin I.; Senn-Irlet, Beatrice (Frontiers in Microbiology, 2017)
Historical datasets of living communities are important because they can be used to document creeping shifts in species compositions. Such a historical data set exists for alpine fungi. From 1941 to 1953, the Swiss geologist Jules Favre visited yearly the region of the Swiss National Park and recorded the occurring fruiting bodies of fungi >1 mm (so-called “macrofungi”) in the alpine zone. Favre can be regarded as one of the pioneers of alpine fungal ecology not least to the fact that he noted location, elevation, geology, and associated plants during his numerous excursions. However, some relevant information is only available in his unpublished field-book. Overall, Favre listed 204 fungal species in 26 sampling sites, with 46 species being previously unknown. The analysis of his data revealed that the macrofungi recorded belong to two major ecological groups, either they are symbiotrophs and live in ectomycorrhizal associations with alpine plant hosts, or they are saprotrophs and decompose plant litter and soil organic matter. The most frequent fungi were members of Inocybe and Cortinarius, which form ectomycorrhizas with Dryas octopetala or the dwarf alpine Salix species. The scope of the present study was to combine Favre's historical dataset with more recent data, either with the “SwissFungi” database or with data from major studies of the French and German Alps, and with the data from novel high-throughput DNA sequencing techniques of soils from the Swiss Alps. Results of the latter application revealed, that problems associated with these new techniques are manifold and species determination remains often unclear. At this point, the fungal taxa collected by Favre and deposited as exsiccata at the 'Conservatoire et Jardin Botaniques de la Ville de Genève' could be used as a reference sequence dataset for alpine fungal studies. In conclusion, it can be postulated that new improved databases are urgently necessary in the near future, particularly, with regard to investigating fungal communities from alpine regions using new techniques.